Implementation of newton divided difference interpolation method on the effects of inflation rate on the unemployment rate in Poland / Nor Faradilah Mahad ... [et al.] - Mahad, Nor Faradilah; Baharudin, Afiqah; Samat, Eaisya Nurfarhana; Nordin, Norazean; Abd Aziz, Nurin Batrisyia (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Poland's economy has done very well over the past 20 years, despite the fact that the country has no natural resources, a low debt leverage, and a slow growth rate compared to other European countries (Piatkowski, 2018). These changes that happen in the process of economic development in Poland contribute to wide representation, especially for Central and Eastern European economies (Hunter and Ryan, 2005). Inflation is a steady rise in prices that can affect a country's economic growth, employment, investment, wealth distribution, social and political situations, and even its social and political climate (Mohseni and Jouzaryan, 2016). A person who is willing to work but is unable to obtain employment is considered to be unemployed (Garrido and Toharia, 2004). Numerous academics have discussed how important it is to control inflation and unemployment for the economic development of various societies (Mohseni and Jouzaryan, 2016). When there is financial stress due to inflation, unemployment rates increase, which means the inflation needs to be controlled from getting higher to lower rates (Singh, 2018). Most people think that when inflation is high and out of the blue, it hurts businesses and consumers and causes people to lose their jobs (Barro, 2013). Singh (2018) examines how inflation is causing issues by increasing the price level and decreasing the purchasing power of money. Besides, inflation also leads to financial problems that affect many people.